2010
DOI: 10.4088/jcp.09m05514yel
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features Associated With Poor Pharmacologic Adherence in Bipolar Disorder

Abstract: Risk for poor medication adherence can be estimated and may be useful in targeting interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 40 publications
5
78
3
1
Order By: Relevance
“…However, this finding may also imply that longer hospitalizations per se are conducive to treatment adherence after discharge. One can speculate that longer hospitalizations allow a more complete remission, resulting in fewer residual symptoms that may impact adherence negatively (Perlis et al, 2010). Furthermore, longer hospitalizations may facilitate individually tailored pharmacotherapy, improving drug effectiveness and tolerability and thus contributing to a more positive patient attitude towards pharmacotherapy (Velligan et al, 2010;Jonsdottir et al, 2013;Baldessarini et al, 2008b).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this finding may also imply that longer hospitalizations per se are conducive to treatment adherence after discharge. One can speculate that longer hospitalizations allow a more complete remission, resulting in fewer residual symptoms that may impact adherence negatively (Perlis et al, 2010). Furthermore, longer hospitalizations may facilitate individually tailored pharmacotherapy, improving drug effectiveness and tolerability and thus contributing to a more positive patient attitude towards pharmacotherapy (Velligan et al, 2010;Jonsdottir et al, 2013;Baldessarini et al, 2008b).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown an association between manic symptoms and non-adherence (Perlis et al, 2010) as well as increased non-adherence in patients that are recovering from mania/hypomania (Baldessarini et al, 2008b). Our findings are likely to reflect the difficulty of managing manic patients in outpatient care, and suggest the need for inpatient care to facilitate proper treatment, an implication further supported by the finding that mania among patients who were diagnosed with bipolar disorder in inpatient care did not predict less prescription fills of prophylactic drugs after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…27 In the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) study of 1771 patients with at least one follow-up visit, cognitive deficit/memory impairment was the only symptom that was presumably an adverse effect and was significantly linked to nonadherence. 28 Although patients on lithium frequently complain of cognitive impairment, prescribing clinicians should be aware that the cognitive deficits in BD patients can, in part, be a manifestation of the disease itself rather than an adverse effect of lithium. 29 A meta-analysis of 12 studies with lithium treatment concluded that lithium's adverse effect on memory is present but limited.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…5, [17][18][19] Nonadherence rates can be as high as 79%. [20][21][22] Long-acting injectable (LAI) antipsychotics have the potential to improve medication adherence.…”
mentioning
confidence: 99%